A contingent view on the importance of inertia and mimicry in location choices by Chinese MNCs. (2016) - Yuan, Lin; Pangarkar, Nitin
This article examines the drivers of international location choices by Chinese multinational corporations. The study draws from prior literature to identify two key drivers of location choice: structural inertia, which implies repeating past choices, and inter-organisational mimicry, which implies following peers. The authors predict that the influence of these forces is contingent on industry and firm characteristics. Specifically, they hypothesise that both structural inertia and internal-organisational mimicry are less salient in high-technology industries and for highly internationalised firms. They also predict that structural inertia and inter-organisational mimicry work as substitutes; that is, when one is strong, the other is weak. Analyses of 661 new entries by 207 Chinese firms in 66 different countries provide strong support for the hypothesised relationships.